Institutional configurations in international investment research - Christopher Weber; Pascal Mayer (Universität Münster, Institut für Organisationsökonomik, 2023)
In the area of International Business (IB), a substantial body of research has accumulated analyzing the effect of various host country characteristics on foreign direct investments (FDI). Special attention has been given to institutions. However, the conventional approach of addressing institutions in IB research has recently been criticized for not paying sufficient attention to the interrelationships among institutions. We address those calls and conceptualize institutions as 'holistic systems composed of interrelated components' (Kim & Aguilera 2016, p. 149) and employ the fuzzy set Qualitative Comparative Analysis (fsQCA) to investigate the interrelated effect of formal and informal institutions on FDI inflows. In our empirical methodology, we use data on FDI and formal and informal institutions from 57 countries. The results support the configurational approach and corroborate a systemic view on the effect of institutions on FDI. Our study contributes to a more nuanced understanding of the workings of institutions on FDI and demonstrate the value in adopting a configurational perspective in institutional research. – – Viele Studien haben sich im Bereich International Business (IB) mit den Auswirkungen verschiedener Ländercharakteristika auf ausländische Direktinvestitionen (ADI) befasst. Insbesondere der Analyse von Institutionen wurde in diesem Zusammenhang besondere Aufmerksamkeit gewidmet. Der herkömmliche Ansatz, Institutionen in der IB-Forschung zu berücksichtigen, ist jedoch in letzter Zeit zunehmend kritisiert worden, da er den Wechselbeziehungen zwischen einzelnen institutionellen Elementen nicht genügend Aufmerksamkeit schenkt. Wir greifen diese Kritik auf und konzeptualisieren Institutionen als 'ganzheitliches System zusammenhängender Elemente' (Kim & Aguilera 2016, S. 149; eigene Übersetzung) und verwenden die Fuzzy Set Qualitative Comparative Analysis (fsQCA), um die zusammenhängende Wirkung von formellen und informellen Institutionen auf ADI-Zuflüsse zu untersuchen. In unserer empirischen Methodik verwenden wir Daten über ADI und formelle und informelle Institutionen aus 57 Ländern. Unsere Ergebnisse unterstützen den Konfigurationsansatz und bestätigen eine systemische Sichtweise auf die Auswirkungen von Institutionen auf ADI. Unsere Studie trägt zu einem differenzierteren Verständnis der Wirkungsweise von Institutionen auf ADI bei und verdeutlicht den Wert der konfigurativen Perspektive in der institutionellen Forschung.
Keywords: D02; F21; F23; 650; Foreign Direct Investment; Institution; International Business; Location Choice; Qualitative Comparative Analysis